Gibt es eine Geographie ohne Raum? Zum Verhältnis von traditioneller Geographie und zeitgenössischen Gesellschaften - Werlen, Benno (ERDKUNDE, 1993)
The idea of human geography as a spatial science may be valuable in the context of pre-modern societies. Because of the embeddedness of these societies, spatial categories allow an approximate description of social and cultural facts, even if they have no spatial existence. Late-modern societies, however, are disembedded. Due to this fact, there is no homogeneous attribution of meaning to spatial facts guided by tradition. Social and cultural universes have no fixed spatial existence. By this, we now discover the real ontology of the social and the cultural: meanings are not rooted in territories or material objects. They are attributed and their attribution may be different far every agent and even for every action. Any so-called spatial argument for the explanation of social action is first subject to the pitfall of the reductionism of vulgar materialism, and second to a misconception: that of the reification of space as a material object. Instead of 'space', geographers should choose 'action' as the key concept. Human geographers, therefore, should no longer try to define their discipline only by stressing the so-called spatial facts. 'Space' is a grammalogue for something else, and because of this we should concentrate on what the grammalogue stands for: materiality as a medium far social processes and social differentiation, a conceptual tool for orientation in the material world, and as grammalogue for farms of absence and presence in direct or anonymous interactions.